If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(m+5)-2(9m+7)=-28(m+3)-2
We simplify the equation to the form, which is simple to understand
-9(m+5)-2(9m+7)=-28(m+3)-2
Reorder the terms in parentheses
+(-9m-45)-2*(9m+7)=-28*(m+3)-2
Remove unnecessary parentheses
-9m-45-2+*(+9m+7+)=-28+*(+m+3+)-2
Reorder the terms in parentheses
-9m-45+(-18m-14)=-28*(m+3)-2
Remove unnecessary parentheses
-9m-45-18m-14=-28+*(+m+3+)-2
Reorder the terms in parentheses
-9m-45-18m-14=+(-28m-84)-2
Remove unnecessary parentheses
-9m-45-18m-14=-28m-84-2
We move all terms containing m to the left and all other terms to the right.
-9m-18m+28m=-84-2+45+14
We simplify left and right side of the equation.
+1m=-27
We divide both sides of the equation by 1 to get m.
m=-27
| 1.5*x=60 | | 1+2v=9+3v | | P(x)=10*7-7 | | 5a+3=-22 | | 8(2n+3)=9(7n+2+3) | | x*8=72 | | 0=16t^2-24t+20 | | -3y-10=7y+10 | | P(x)=10*10-7 | | -2(t-2)+9t=3t-4 | | -9=12y+3 | | 7x+3=-8+3x+23 | | 18=7b+4 | | -9-4= | | 5p-14=26 | | 6-6(a+2)=8+a | | A+1.5=6 | | 1.7x=5.61 | | x^2=650 | | -(-5-6)=4(5x+3) | | P(x)=x(50x^2+30x)-90 | | -2(t-1)+4t=6t-6 | | P(x)=x(50x^2+30x) | | -12=x-15 | | 4x^2=576 | | -2(x-3)=x+9 | | .2y=16 | | .96y-.79=.21y+.46 | | 14x+7=45x+390000 | | 3(58-8)= | | a^2b-2ab^2+b^3=0 | | 2(x-2)-3=6x-4(3+x) |